The folk concept of lying. Issue 8 (31st July 2019) - Wiegmann, Alex; Meibauer, Jörg
Abstract: Lying is a familiar and important concept for virtually all of us, and philosophers have written a lot about what it means to lie. Although it is commonly accepted that an adequate definition of lying captures people's use and understanding of this concept, there have been surprisingly few empirical studies on it. n recent years, however, there is a trend emerging to remedy this lacuna. In this paper, we provide an overview of these studies. Starting from a widely accepted philosophical definition of lying, we focus on the following three questions: Is an intention to deceive required for lying? Is it possible to lie despite saying something true? Can you lie by falsely implicating?